E-Commerce Growth and Development, Impact, and Challenges in Indonesia - Mahmuddin,; Ningrum Natasya Sirait, (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2022)
This paper focused on how e-commerce growth and development, impact, and challenge in Indonesia. This topic is quite interesting to discuss simply because digital law and business are quite new to Indonesian lawmaker. Overall, this paper also shows how the e-commerce regulation shape Indonesia digital trade law. Besides that, some of discussion also talk about how financial technologies provider involved on e-commerce growth. It is true that most e-commerce in Indonesia cooperates with fintech in terms of payment services. The growth and development of fintech somehow help e-commerce to grow and evolve. It is also important to discuss how the law support the e-commerce. Most of law area cover information and electronic transaction, intellectual property, and consumer protection. Not only that, but this paper also shows a real case involved three main e-commerce in Indonesia involving Go-Jek (ride-shared services and food deliveries platform), Tokopedia (marketplace), and Traveloka (travel and leisure). Finally, we also see how the main challenges such us human resources, funding, and cybersecurity will impact the e-commerce growth and development in Indonesia.